(3QSGdI JbdjO GdTjN CHj GdcJGjHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG hMOg GdefLR dYHOg hYOg HGdHjVGA hLejY HdOGf GdUYjO ef fTQ OYhI GdMb hCNP GdejKGb s
(3BNQgG (B:s
(3hGdSdGe Ydjc hQMeI hdjg LGQjI Edjc hGdMeO dehdGfG hMOg GdMGce GdefaQO Y GdJMOjO hGdTcQ dhdjg GdgGOi Edi Ojf GdJhMjO Je GdJbdjO HefI hdi GdCeQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B47s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis